VD_FINDINFO HC / 2024 / 355 vom 4. September 2024 - VD Tribunal cantonal (2024)
RESPONSABILITÉ DE L'EMPLOYEURRAPPORT OBLIGATIONNEL, CONTRAT DE TRAVAIL, INDEMNITÉ JOURNALIÈRE | 319 CO, 322 al. 1 CO, 97 al. 1 CO